Antiretroviral drug–drug interactions: A comparison of online drug interaction databases. (4th September 2022) - Drwiega, Emily N.; Badowski, Melissa E.; Michienzi, Sarah
Abstract: What is known and objective: Antiretrovirals have a high drug interaction potential, which can lead to increased toxicity and/or decreased efficacy. Multiple databases are available to assess drug–drug interactions. The aim of our study was to compare interaction identification for commonly used ARVs and concomitant medications between six different online drug–drug interaction databases. Comment: This was a cross‐sectional review using each of the following six databases: LexiComp®, Clinical Pharmacology®, Micromedex®, Epocrates®, University of Liverpool, and University of Toronto. Sixteen antiretroviral drugs and 100 of the DrugStats Database "Top 200 of 2019" list of medications were included. Each of the six databases identified a different number of actual or potential interactions. The number of interactions ranged from 211 to 283. What is new and conclusions: A variety of databases exist with inconsistent identification of actual or potential drug–drug interactions amongst them. It may be beneficial to cross‐reference multiple databases prior to making decisions regarding patient care. Abstract : Actual or Potential Drug–drug Interactions Identified.